All in a day's work : student nurses' perceptions of their clinical learning experiences in a corporate workplace context - Volschenk, Mariette (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Centre for Health Science Education))--University of Stellenbosch, 2009.